2013
DOI: 10.1007/s40268-013-0018-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Crushed Ticagrelor Tablet Doses: Recovery Following Crushing and Naso-gastric Tube Passage Ex Vivo

Abstract: BackgroundOrally available ticagrelor in combination with low-dose aspirin (75–100 mg/day) is indicated for adult patients with acute coronary syndromes. However, patients with swallowing difficulties may be unable to consume the currently available 90-mg tablet. It is hypothesized that ticagrelor could be given to this patient cohort as a crushed dose administered either orally or via a naso-gastric (NG) tube.ObjectivesTo investigate the potential use of crushed ticagrelor tablets (90- and 180-mg doses) for o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…They found that ≥97% of the active substance from one original tablet is delivered through the NGT. However, this study is limited by the high volume of water for flushing the mortar and the NGT (150 mL), which is often inapplicable in critical care [4]. On the other hand, Kotake et al [5] found that approximately 30% of amiodarone from tablets is lost during administration via NGT.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…They found that ≥97% of the active substance from one original tablet is delivered through the NGT. However, this study is limited by the high volume of water for flushing the mortar and the NGT (150 mL), which is often inapplicable in critical care [4]. On the other hand, Kotake et al [5] found that approximately 30% of amiodarone from tablets is lost during administration via NGT.…”
Section: Introductionmentioning
confidence: 91%
“…Crean et al [4] conducted an ex vivo study investigating the administration of crushed ticagrelor tablets via NGT. They found that ≥97% of the active substance from one original tablet is delivered through the NGT.…”
Section: Introductionmentioning
confidence: 99%
“…Previously reported studies showed that the administration of crushed ticagrelor increased both ticagrelor and its active metabolite concentration in human plasma [11,12]. Additionally, in patients treated with crushed ticagrelor, earlier inhibition of platelet aggregation was observed, compared to the reports in which the integral tablets were given [13,14].…”
Section: Introductionmentioning
confidence: 93%
“…(9,10) Recently, crushed ticagrelor tablets, administered orally or via a naso-gastric tube, has been shown to be feasible and resulted in increased plasma concentration of ticagrelor and its active metabolite at an earlier time point compared to integral tablets. (11,12) As the plasma concentration of ticagrelor and its active metabolite is linearly associated with the degree of platelet inhibition, (2) administration of crushed or chewed ticagrelor may provide a more rapid onset of drug action. Nevertheless, limited pharmacodynamic data of novel methods of ticagrelor administration exist and data regarding chewed ticagrelor have not been reported.…”
Section: Introductionmentioning
confidence: 99%